U.S-China relations [ China policy on Capitol Hill - Xie, Tao , 1973- (Routledge contemporary China series, 2009)
Explores relations between the US and China, focusing in particular on China policymaking in the US Congress. This book is based on an analysis of China bills introduced in Congress over three decades. It provides analysis of how Congressional policymaking works in practice, and explores the controversial issues in US-China relations